2019
DOI: 10.1089/jwh.2018.7380
|View full text |Cite
|
Sign up to set email alerts
|

Trends Over Time in Pap and Pap-HPV Cotesting for Cervical Cancer Screening

Abstract: Background: In 2012, updated cervical cancer screening recommendations were released with consensus on Papanicolaou (Pap) testing every 3 years for women age 21-65 years or Pap-human papillomavirus (HPV) cotesting at 5-year intervals for women age 30-65 years. Primary study aims: Assess current use of Pap-HPV cotesting and describe local population trends over time in Pap and Pap-HPV cotesting. Secondary aim: Assess sociodemographic factors correlating with screening. Methods: We assessed Rochester Epidemiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 29 publications
3
46
2
Order By: Relevance
“…However, the result is lower than a finding from European countries that the coverage of cervical cancer screening tests ranges from 10% to 79% [81]. Consistent with the European report, a study in Minnesota, United States of America, showed that 60.8% of women had received Pap-HPV co-test screening with a significant increment among women aged 30-65 years, from 10.0% in 2007 to 60.8% in 2016 [82]. It is also lower than other findings across the literature: Kenya, 16.4% [83], India, 29.8% [84], South Africa, 52% [85], and China, 20.7% [86].…”
Section: Plos Onementioning
confidence: 76%
“…However, the result is lower than a finding from European countries that the coverage of cervical cancer screening tests ranges from 10% to 79% [81]. Consistent with the European report, a study in Minnesota, United States of America, showed that 60.8% of women had received Pap-HPV co-test screening with a significant increment among women aged 30-65 years, from 10.0% in 2007 to 60.8% in 2016 [82]. It is also lower than other findings across the literature: Kenya, 16.4% [83], India, 29.8% [84], South Africa, 52% [85], and China, 20.7% [86].…”
Section: Plos Onementioning
confidence: 76%
“…Despite recommendations against annual cervical cancer screening from major guideline developing groups, and many years since annual cytology screening was recommended, it is reported that annual cytology testing still is common 160,161 . Likewise, adoption of the 2012 preferred strategy of cotesting for women aged 30 to 65 years had been slow, although recent reports show an upward trend in cotesting among individuals aged 30 to 65 years, 24,25,162 which varied geographically, from 27.5% in Utah to 49.9% in the District of Columbia 163 . Not only is guideline adherence an enduring challenge; but, as noted previously, concerns about lack of universal access to preferred screening tests overall, and more so outside of urban and academic settings, have been borne out by national surveys of laboratories 22,134 …”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are notable disparities regarding screening approaches offered to different populations. Black and Hispanic women are more likely than white women to be screened with cervical cytology alone than with HPV alone or co-testing ( MacLaughlin et al, 2019 ). Since a negative cervical cytology result provides less reassurance against the development of cancer than HPV testing or co-testing ( Castle et al, 2018 ), screening needs to be repeated more often to provide equivalent protection ( Curry et al, 2018 ).…”
Section: Lessons From the Pandemic: How To Improve Resilience And Equity In Cervical Cancer Screeningmentioning
confidence: 99%